Housing collateral and home-equity extraction - Simon Juul Hviid; Alessia De Stefani (Danmarks Nationalbank, 2019)
We study the effect of house price developments on home-equity extraction and household expenditure, exploiting data covering the population of Danish homeowners between 2009 and 2016. Our findings indicate that house price increases affect home-equity extraction - and more so for homeowners close to their borrowing limits. Furthermore, the effect of house prices on expenditure is entirely driven by home-equity extraction. Our results indicate that the mortgage system plays an important role for the transmission of housing wealth increases to the real economy.
Keywords: D12; D14; R32; 330; Mortgage decisions; house prices; origin-push migration